LEXICAL EXPRESSION OF GENDER IN THE ENGLISH LANGUAGE - Khidirova Shakhnoza Gafforovna (Western European Studies, 2025)
This article provides a theoretical analysis of the lexical expression of gender in the English language, the reasons for the persistence of gender inequality in language, and the extent of usage of feminine terms. It examines how grammatical gender, referring to both animate and inanimate entities, is expressed in English through actual linguistic examples.
Keywords: English language; gender; lexical layer